(untitled) (TEL Tempo, Espaço e Linguagem, 2025)
The last emperor of Brazil, Dom Pedro II, was also known as an erudite monarch, interested in the arts, humanities and technical sciences. His various visits abroad allowed him to establish relationships not only with frequent political figures, but also with many renowned artists and scientists. His visits to France were no exception, and it was with particular interest that the Brazilian monarch established relations in the south of France.